A STUDY ON STUDENTS’ ABILITY IN READING DESCRIPTIVE TEXT; A CASE STUDY AT SMAN 1 SIKUR - Rosyidi, Ahmad Zuhri; Darmanto, Darmanto (Journal of Languages and Language Teaching, 2020)
This study was intended to find out the students? ability in reading descriptive text. Reading skills are considered as an important skill and are uneasy to acquire. In this study, there were 40 students of the second year students of SMAN 1 Sikur are involved as the subject of this study. The method used in this research is a quantitative study. In collecting the data, the writer used a reading test. The data were analyzed through basic statistical computation. To find out their ability and difficulties in reading descriptive text, the test was used which consists of 25 items to students in the form of multiple choice. The test score for each item was 0.4 points. The result of data analysis showed that the mean score of the second year students of SMAN 1 Sikur in reading the descriptive text was fairly good. There were 21 (52.5%) students who were in a high position and 19 (47.5%) students were in a low position. Although 52.5% of students in a high position and 47.5% in a low position, the students? mean score shows a low position, it is 7.2 mean score which classified as fairly good. Therefore, the ability of the second year students of SMAN 1 Sikur has not been in a high position which is categorized from excellent to good score level. This is caused by the lack of reading strategy and vocabulary. The two weaknesses become students? difficulties in reading descriptive text.